Calcutta the stormy decades - Sarkar, Tanika (Ed.); Bandyopadhyay, Sekhar (Ed.) (New Delhi Social Science Press, 2015)
Contributed articles.
Ordering the urban space War, famine and unrest Communal relations:solidarities and violence Postcolonial transition
Keywords: COMMUNALISM; HISTORY